2008
DOI: 10.4102/sajip.v34i2.474
|View full text |Cite
|
Sign up to set email alerts
|

The cross-cultural application of the social axioms survey in The South African police service

Abstract: The objectives of this study were to investigate the replicability, construct equivalence, item bias and reliability of the Social Axioms Survey (SAS) in the South African Police Service (SAPS). A cross-sectional survey design was used. the participants consisted of applicants who had applied for jobs in the SAPS (n = 1535), and the SAS was administered to them. An exploratory factor analysis utilising target rotation applied to all 60 items of the SAS revealed four interpretable factors (Social Cynicism, rewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Social Complexity and Fate Control had shown marginal reliability as some previous researches [ 17 ]. The Social Complexity factor thus remains problematic; this is the same factor from the original social axioms survey that Barnard et al [ 4 ] were unable to replicate in their South African study.…”
Section: Discussionmentioning
confidence: 99%
“…Social Complexity and Fate Control had shown marginal reliability as some previous researches [ 17 ]. The Social Complexity factor thus remains problematic; this is the same factor from the original social axioms survey that Barnard et al [ 4 ] were unable to replicate in their South African study.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from South Africa Barnard, Meiring and Rothmann (2008) investigated the SAS's construct equivalence, item bias and reliability in the South African context using a sample drawn from the South African Police Service (SAPS). They reported that only four interpretable factors were consistent with Barnard et al's (2008) study the SAS construct of Social Complexity also did not replicate. Hence these two scales (Fate Control and Social Complexity) needed to be improved (Leung et al, 2012).…”
Section: The Evolution Of the Social Axioms Survey (Sas)mentioning
confidence: 92%
“…Drawing on Rotter's (1966) characterisation of locus of control, Leung and Bond conceptualise social axioms as generalised expectancies about the world and how it works, typically taking the form A  B and may be causal or correlational. Beginning with qualitative research in Hong Kong and Venezuela and using some items culled from the literature, their collaborative team developed a measurement scale, collected data in over 40 cultures and identified social axiom dimensions at the levels of individuals and nations, which include South Africa (university students, Bond & Leung, 2009;Bond, Leung, Au, Tong, De Carrasquel et al, 2004) and (police recruits, Barnard, Rothmann & Meiring, 2008).…”
Section: Introductionmentioning
confidence: 99%